La Sezione teatrale del Museo nazionale di San Martino: storia delle trasformazioni di «una perfetta e perenne memoria di comici sommi e carissimi a Napoli» - Saviano, Carmela (Drammaturgia, 2020)
The essay analyzes the history, from its origins to the present day, of the Theatre Section of the National Museum of San Martino, emphasizing the relationships between the staging choices made over the years, and the articulated events of the Neapolitan theatrical life. The survey, carried out through an unprecedented comparison between the sources and the documents collected, preserved and carefully ordered in the Institute’s Historical Archive in over one hundred and fifty years, constitutes a contribution to the knowledge of a museum reality that still awaits an overall museographic and museological revision. Born at the behest of Vittorio Spinazzola around the end of the 19th century, the ‘empathic’ space dedicated to the Neapolitan theatre in the city museum since the third decade of the Twentieth Century has undergone a gradual process of marginalization generated by aesthetic logics. Only in recent years, while still awaiting a decisive relaunch in terms of local development and active participation of citizens, it has been brought to the attention of the public, thanks to the opening of new viable perspectives towards the enhancement of the museum’s theatrical heritage.